ONTOLOGI, EPISTEMOLOGI, AKSIOLOGI DALAM PENDIDIKAN KARAKTER - Elfira Rahmadani; Dian Armanto; Ely Syafitri; Reza Umami (Smart Education, 2021)
Abstract: Character education is useful for building the character of each individual so that they can become individuals who can have benefits for the individual and the surrounding environment. This study examines and describes how to conceptualize the theoretical basis of character education and how to implement the theoretical basis of character education. This study examines and describes how to conceptualize the foundation of character education theory and how to implement the foundation of character education theory. The foundation of character education theory includes the foundation of ontology, epistemology foundation and axiology foundation. In this case the researcher can explain how the conceptualization and implementation of the foundation of ontology, epistemology and axiology of character educationÂ Â Keyword: Ontology Platform, Epistemology, Axiology and Character EducationÂ